2023
DOI: 10.1039/d2ma00999d
|View full text |Cite
|
Sign up to set email alerts
|

Configuration dependent photovoltaic properties of cyclometalated heavy metal complexes for organic solar cells

Abstract: Cyclometalated heavy metal complexes as a new class of photovoltaic materials have attracted specific attention owing to their triplet feature, which is expected to be beneficial for longer exciton diffusion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…[46] Studies revealed that exciton diffusion length can be increased by use of donor or acceptor materials which contain heavy atoms that permit intersystem crossing and by doping active layer with triple sensitizers. [47] Yang et al [48] investigated electron donor materials of 2-(5 00 -tert-butyl-[2,2 0 :5 0 ,2 00 -terthiophen]-5-yl)benzo [d]thiazole (tTBz) ligand, platinum (II) complex (tTBzPt), octahedral homoleptic iridium (III) complex (tTBz3Ir), and octahedral heteroleptic tTBzIr complex for OPVs. The molecular geometries of these donor materials were investigated using density functional theory (see Figure 2B).…”
Section: Exciton Diffusionmentioning
confidence: 99%
“…[46] Studies revealed that exciton diffusion length can be increased by use of donor or acceptor materials which contain heavy atoms that permit intersystem crossing and by doping active layer with triple sensitizers. [47] Yang et al [48] investigated electron donor materials of 2-(5 00 -tert-butyl-[2,2 0 :5 0 ,2 00 -terthiophen]-5-yl)benzo [d]thiazole (tTBz) ligand, platinum (II) complex (tTBzPt), octahedral homoleptic iridium (III) complex (tTBz3Ir), and octahedral heteroleptic tTBzIr complex for OPVs. The molecular geometries of these donor materials were investigated using density functional theory (see Figure 2B).…”
Section: Exciton Diffusionmentioning
confidence: 99%
“…34 Furthermore, through systematic modification of the ligand conjugation lengths and alternation of intra-ligand charge transfer behavior, as well as optimization of spatial configuration from heteroleptic to homoleptic Ir complexes, the PCE for smallmolecule cyclometalated Ir complexes based electron donor materials could be enhanced from o4% of (TBz) 2 Ir(acac):PC 71 BM to 410% of homoleptic TBz3Ir:Y6 and eTBz3Ir:L8BO. 25,[28][29][30][35][36][37] It has been noted that previous reports for small-molecule Ir complex-based BHJ OSCs were mainly concentrated on the development of new materials, and studies on device engineering have been rarely performed. The only recent example is the introduction of a bilayer device structure to improve the PCE from 3.91% for (TBz) 2 Ir(acac):PC 71 BM BHJ to 6.17% of bilayer PDCBT/(TBz) 2 Ir(acac):PC 71 BM.…”
Section: Introductionmentioning
confidence: 99%
“…34 Furthermore, through systematic modification of the ligand conjugation lengths and alternation of intra-ligand charge transfer behavior, as well as optimization of spatial configuration from heteroleptic to homoleptic Ir complexes, the PCE for small-molecule cyclometalated Ir complexes based electron donor materials could be enhanced from <4% of (TBz) 2 Ir(acac):PC 71 BM to >10% of homoleptic TBz3Ir:Y6 and eTBz3Ir:L8BO. 25,28–30,35–37…”
Section: Introductionmentioning
confidence: 99%
“…14 ally, organometallic Ir-and Pt-based complexes were incorporated into both fullerene and nonfullerene acceptor OPVs, with improved PCE due to enhanced absorption, extended exciton lifetime, and increased charge transport. 15 Furthermore, tellurophene-based triplet harvesting materials serve as acceptors for OPVs and contribute to an increased PCE because of long exciton lifetime and improved diffusion length. 16 Bi et al demonstrated a reduction of nonradiative recombination loss due to enlarged exciton diffusion length, which led to an improvement in PCE of the OPV.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, the phosphorescent sensitizer fac -tris­(2-phenylpyridine) iridium [Ir­(ppy) 3 ] exhibits long-lifetime triplet states and allows an increase in exciton diffusion length, resulting in ∼80% power conversion efficiency (PCE) improvement compared to control groups . Additionally, organometallic Ir- and Pt-based complexes were incorporated into both fullerene and nonfullerene acceptor OPVs, with improved PCE due to enhanced absorption, extended exciton lifetime, and increased charge transport . Furthermore, tellurophene-based triplet harvesting materials serve as acceptors for OPVs and contribute to an increased PCE because of long exciton lifetime and improved diffusion length .…”
Section: Introductionmentioning
confidence: 99%